Modeling of Phonoelastic and Strain-stress Properties of ¹³C High Pressure Sensor for Use in Ecological Safety and Use of Natural Resources - Kondrat’yev, A.I. (Екологічна безпека та природокористування, 2009)
We investigate different properties of ¹³C diamond layer which was grown on a top of a brilliant cut diamond anvil. We connected equations of state for diamond with stress and strain concentrating on the case of [100], see ([1]) strain with diamond anvil bearing load plane as (100), (see [1]). We investigated the behavior of optical Г phonons with respect to pressure, strain and stress parameters. We also did simulation of these problems using finite element modeling and Nike2D computer software. We used O.H. Nielsen approach for modeling of the sensor.